Gender equality in smart sustainable cities: literature review - Ababneh, Alaa; Lok, Ka Leung; Abdeyazdan, Hossein; Opoku, Alex; Chen, Charles (Frontiers in Sustainable Cities, 2025)
IntroductionThe 2030 Agenda for Sustainable Development Goals (SDGs) has garnered significant attention globally, emphasizing the need for achieving the 17 goals that promote sustainable development. Among these, the fifth goal focuses on gender equality, which has become increasingly important in various nations. Notably, there is a recognized connection between SDG 11, which pertains to sustainable cities, and SDG 5. The concept of smart cities under SDG 11 is viewed as pivotal in enhancing gender equality. However, existing research exploring the relationship between smart cities and gender equality remains limited.MethodsThis study employs a bibliometric review technique utilizing the Bibliometrix tool to conduct a comprehensive analysis of literature related to SDG 5, SDG 11, and smart cities. This method allows for an extensive examination of existing research articles to identify trends and themes within the literature.ResultsThe analysis revealed that many research articles frequently cited terms associated with sustainability, community, design, transportation, and mobility. It was found that most studies focusing on SDG 5 and SDG 11 through the lens of smart cities primarily aim to: (1) Understand and promote sustainability principles. (2) Address social issues. (3) Develop inclusive solutions. (4) Improve transportation for women and their commuting needs. Additionally, there is a noted increase in scholarly interest regarding health and climate issues about SDGs 5 and 11.DiscussionThe findings indicate a significant gap in the literature concerning the interplay between smart cities and gender equality, suggesting that further research is necessary to understand this relationship fully. The emphasis on sustainability principles and inclusive solutions highlights the potential for smart city initiatives to contribute positively to gender equality. As interest in health and climate issues grows within this context, it underscores the need for integrated approaches that address multiple dimensions of sustainable development while promoting gender equity.